A narrative inquiry of language teachers’ perceptions and experiences in using WhatsApp during New Normal Post-Covid-19 era - Irfan Suryana; Vicky Hidantikarnillah; Didik Murwantono (Universitas Islam Sultan Agung, 2021)
The purpose of this inquiry is to explore and make sense of the stories of language teachers’ perceptions and experiences in using WhatsApp during New Normal Post-Covid-19 era. More specifically, the study is intended to understand the popularity and the usage of WhatsApp in the process of teaching and learning. To achieve the purpose of the study, a narrative inquiry is employed. Four language teachers of SMA Maarif Yogyakarta participated in this study and shared their perceptions and experiences in using WhatsApp as learning medium during New Normal Post-Covid-19 era. The online interview was used to collect information from the teachers by using Google Form. The findings of this narrative inquiry indicate that WhatsApp is a popular learning medium and the use of WhatsApp in distance online learning during New Normal Post-Covid- 19 era in SMA Maarif Yogyakarta is really effective compared to other learning media such as Google Classroom or Zoom and the language teachers give positive reactions regarding the application.